Classroom Management by Physical Education Teachers and Pedagogues Working in the Municipal Education System of Jacareí (Interdisciplinary Studies Journal, 2024)
Classroom management is essential in teacher training courses. From the perspective of Physical Education teachers and classroom instructors in the Municipal Education Network of Jacareí, in the state of São Paulo, this mixed-methods, exploratory, and descriptive case study researched 34 Physical Education professionals (26 experienced and 8 inexperienced) and 96 Pedagogues (85 experienced and 11 inexperienced) working in Elementary School I, across 29 schools of the Jacareí Municipal Education Department. Of the 34 (24.1%) Physical Education teachers, 8 consider themselves inexperienced, 2 slightly competent, 1 very competent, and 5 partially competent. Among the 26 experienced teachers, 5 consider themselves slightly competent, 15 partially, 5 very competent, and 1 extremely competent. Among the 96 (68.1%) pedagogues, 11 are inexperienced; 3 consider themselves very competent, 5 partially competent, and 3 slightly competent. Of the 85 experienced pedagogues, 3 consider themselves extremely competent, 20 very competent, 49 partially competent, 12 slightly competent, and 1 completely incompetent. The initial training of professionals in both fields, working in Jacareí-SP, was deficient and did not provide concrete and practical information on classroom management and student supervision. Both experienced and inexperienced professionals in both areas studied struggle to manage their students effectively in the classroom.
Keywords: Classroom management; Physical Education; Pedagogues; Initial training